2022
DOI: 10.3390/ijerph191912085
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pilates Training on Body Composition and Isokinetic Muscular Strength in Adolescent Baseball Players

Abstract: Body composition and muscular strength are important for baseball skills and successful performance. Conditioning training programs have the potential to enhance athletic performance via physiological changes. In this single-group interventional study, we investigated the effect of 8 weeks of Pilates training (PT) on contralateral and regional body composition, and isokinetic muscular strength in knee and trunk flexion/extension in adolescent baseball players. In our results, PT increased both right- and left-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In summary, numerous studies have identified various benefits of Pilates for their practitioners (Yook et al, 2022 ). The influence of Pilates on posture and movement quality due to flexibility or strength is well documented (Xu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, numerous studies have identified various benefits of Pilates for their practitioners (Yook et al, 2022 ). The influence of Pilates on posture and movement quality due to flexibility or strength is well documented (Xu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature lacks clinical trials that provide evidence on the effects of low-cost and easily accessible training programs that are effective for the under-13 and under-15 soccer categories. Pilates emerges as a viable option that could be recommended as a complementary method to strengthen the muscles that contribute to the to body posture and, consequently, enhancing athletes’ performance, particularly during the growth phase [ 9 , 10 , 11 , 12 ]. It would make an important contribution to trunk stabilization and allow children to perform better in sports by working deeper muscles.…”
Section: Introductionmentioning
confidence: 99%
“…It would make an important contribution to trunk stabilization and allow children to perform better in sports by working deeper muscles. As the muscles and bones are in the formation phase, the correct stimulus could lead to the best static body posture and for sporting gestures [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations